Dinamika Perkembangan Pondok Pesantren Mamba’u Usulil Hikmah Dukuh Nglaban Kecamatan Kedawung Kabupaten Sragen Tahun 1998-2024 - Abdul Rasyid Nur Effendi; Moh. Mahbub; Aly Mashar; Moh. Ashif Fuadi (Keraton: Journal of History Education and Culture, 2026)
This study aims to examine the dynamics of the development of Mamba'u Usulil Hikmah Islamic Boarding School located in Nglaban Hamlet, Sragen, during the period 1998–2024. The study focuses on institutional growth, transformation of the educational system, and the supporting and inhibiting factors influencing its development. This research employs a historical method with a qualitative approach, including heuristics, source criticism, interpretation, and historiography. Data were collected through interviews, documentation, and literature review. The findings indicate that the pesantren has undergone significant and dynamic development, evolving from an initial modest establishment into a more organized and adaptive Islamic educational institution. This transformation is reflected in curriculum development integrating traditional (salaf) and formal education, an increase in the number of students, and improvements in facilities and infrastructure. The main supporting factors include charismatic kyai leadership, strong community support, and the institution’s adaptability to social changes. Meanwhile, the inhibiting factors consist of limited resources in the early stages and challenges posed by modernization. This study concludes that the success of the pesantren’s development lies in its ability to preserve traditional values while continuously innovating in education.